The awareness of disaster recovery among universiti students: A case study on Universiti Utara Malaysia volunteers - Basumi, Kusna; Abdul Nifa, Faizatul Akmar (2017)
Disaster management is intended to ensure that disaster occurrences can be managed and controlled with systematic and sustainable methods.It is important for each community to learn about the phases of disaster management, particularly the recovery phase.It is also important to encourage university students to be exposed to volunteerism programs so that they have additional skills and interest that can be used when they are out of the university environment.This study is conducted in Universiti Utara Malaysia (UUM) with the aims to explore and identify the level of awareness among students regarding the recovery phase of the disaster management and their knowledge of volunteerism.The findings of this study found that university students understand the knowledge of volunteerism in disaster. Besides, university students show that they have awareness on disaster recovery and sympathize with the disaster victims, which motivate them to volunteer for disaster recovery.The data for this study is collected using qualitative methods. The data gathered will help identify the level of awareness and knowledge of volunteering among UUM university students. This data will be useful for the UUM management to organize appropriate disaster recovery awareness campaigns based on the findings in this study to provide relevant skills training to all student volunteerism at UUM.